Adsorption and dissociation of a single water molecule on graphene-like ZnO monolayer with oxygen vacancies: a first-principles study. (1st March 2023) - Yang, Ruijie; Du, Yanping
Abstract: ZnO monolayer (ZnO-ML) is a novel two-dimensional (2D) nanomaterial with a structure and characteristics similar to graphene. The interaction between water molecules and ZnO-ML especially oxygen vacancy (VO ) decorated ZnO-ML (VO -ZnO-ML) has not been investigated yet. First-principles calculations are used to comprehensively investigate the adsorption configurations, electronic properties, and adsorption energy of a single H2 O molecule on ZnO-ML. The H2 O molecules and ZnO-ML interact strongly, with H2 O serving as the charge accepter. ZnO-ML can maintain its nonmagnetic feature following the adsorption of H2 O and the introduction of VO . For the H2 O dissociation process on pure ZnO-ML, the reaction energy ( E r ) is 95.03 kJ ml −1 and the energy barrier ( E bar ) is 167.54 kJ mol −1, respectively. The presence of VO can remarkably decrease the E bar and E r to half. Moreover, the E bar and E r can be further reduced with the increase of the VO density. The hydroxyl groups can stably exist on ZnO-ML, and the adsorption becomes stronger with the increase of the VO density. These findings provide details of the interaction between H2 O and ZnO-ML, thereby facilitating the further research of 2D ZnO nanomaterial in photocatalysis, electrocatalysis, and smart devices.